Design and Performance Evaluation of a PLC- and Fuzzy Logic-Based Control System for Improving Thermal and Humidity Distribution in Cold Storage Environments - Sandy Dwi Kurniawan; Mochammad Rusli; Erni Yudaningtyas (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2025)
Perishable agricultural commodities such as vegetables and fruits are susceptible to environmental storage conditions, particularly temperature and humidity, which significantly impact their quality. This study addresses the critical issue of uneven temperature and humidity distribution in cold storage environments, which can lead to spoilage and reduced product quality. Utilizing Computational Fluid Dynamics (CFD) simulations from ANSYS software, airflow and thermal distribution patterns were analyzed. A fuzzy logic control system was then developed using MATLAB and integrated with a Programmable Logic Controller (PLC) to regulate key actuators—servo motor, fan, and mist maker—based on real-time environmental parameters. Simulation results demonstrated that the fuzzy-controlled system achieved the target temperature setpoint of 21?°C efficiently, with minor fluctuations: ±0.15?°C to ±0.30?°C. The study confirms that intelligent control systems significantly enhance environmental uniformity in cold storage, thereby improving the preservation of perishable goods.